Trends of Mycoplasma genitalium infections in Berlin, Germany, 2017–2023 - Roger Dumke; Tobias Glaunsinger (Journal of Global Antimicrobial Resistance, 2025)
ABSTRACT: Objective: The cell wall-less species Mycoplasma genitalium is a sexually transmitted pathogen with a strong tendency to acquire resistance. Current knowledge on trends of resistance rates and differences between the at-risk population of men who have sex with men (MSM) and heterosexual patients, as well as on circulating genotypes in both groups, is limited. Methods: Between August 2017 and December 2023, M. genitalium strains in 373 samples from patients (MSM: n = 269, non-MSM: n = 104) consulting at a specialized sexually transmitted infection practice in Berlin, Germany, were characterized by molecular methods to detect the presence of mutations associated with macrolide (23S rRNA) and quinolone resistance (parC), and to determine the MgpB strain type. Results: Overall, 37.5% of MSM and 30.8% of heterosexual patients carrying M. genitalium were asymptomatic. Among MSM, the rate of macrolide resistance remained relatively constant during the investigation period (mean: 85.9% of strains), whereas quinolone resistance (mean: 19.7%% of strains) increased from 6.8% (2017) to approximately 38% (2021–2023). In contrast, mean resistance rates of 42.2% for macrolides and 12.5% for quinolones were measured in strains from heterosexual patients. The most common MgpB strain types were types 4 (MSM: 38.4%) and 7 (non-MSM: 16.7%). Conclusions: The results of this study confirm a constantly high rate of macrolide-resistant M. genitalium strains and a trend of increased quinolone resistance among MSM in an urban environment. Despite lower rates, the percentage of resistant strains in heterosexual patients has also reached an alarming extent. The determination of MgpB strain types provides insights into the distribution of genotypes of an important agent of sexually transmitted infections in both population groups.